Knowledge, attitudes, and practices of inpatients with chronic cardiovascular comorbidities regarding polypharmacy: a cross-sectional study - Xu, Lijun; Zhuo, Chenggui; Xu, Hongyan; Xia, Zhelin; Wu, Meicui; Cai, Haipeng (Frontiers in Pharmacology, 2025)
BackgroundWith the increasing prevalence of chronic cardiovascular diseases and the widespread use of multiple medications, polypharmacy has become a significant concern in patient management. This study aimed to examine the knowledge, attitudes, and practices (KAP) of patients with chronic cardiovascular comorbidities, such as coronary artery disease (CAD), hypertension, diabetes, and hyperlipidemia, concerning polypharmacy.MethodsA cross-sectional study was conducted among hospitalized patients from June 1 to 16 December 2024, utilizing a validated questionnaire-based survey to collect data. The self-made questionnaire included demographic information and an assessment of participants’ KAP scores related to polypharmacy.ResultsA total of 706 valid responses were obtained. Of these, 493 participants (69.83%) were males, 342 (48.44%) were aged 65 years or older, and 347 (49.15%) resided in rural areas. The mean knowledge, attitude, and practice scores were 3.62 ± 2.52 (possible range: 0–7), 28.56 ± 3.97 (possible range: 10–50), and 17.55 ± 3.55 (possible range: 5–25), respectively. Structural equation modeling (SEM) further demonstrated that, among individuals taking five or more medications daily, knowledge exerted a positive direct effect on both attitude (β = 0.28, P < 0.001) and practice (β = 0.41, P < 0.001), while attitude also positively influenced practice (β = 0.39, P < 0.001). Moreover, an indirect pathway from knowledge to practice through attitude was suggested by the SEM results (β = 0.11, P < 0.001).ConclusionInpatients with chronic cardiovascular comorbidities exhibited insufficient knowledge and negative attitudes, with notable gaps in adherence behaviors regarding polypharmacy. These findings highlight the need for targeted educational interventions to enhance patients’ knowledge and attitudes toward polypharmacy, and to support safer and more consistent medication practices.